2022
DOI: 10.1007/s10198-022-01506-1
|View full text |Cite
|
Sign up to set email alerts
|

Were we happy and we didn’t know it? A subjective dynamic and financial assessment pre-, during and post-COVID-19

Abstract: The COVID-19 pandemic has brought many changes into people’s lives. Fear, job insecurity, changes in their financial stability, concerns about their future lives have changed the entire lives of people and have affected the cognitive well-being of individuals. The purpose of the present analysis is to measure how the COVID-19 pandemic, along with financial factors, has affected the perceived level of well-being of individuals. We are also interested whether there are differences between life before COVID-19, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…During the pandemic, confusion from mixed COVID-19 messages, different national guidelines, and the uncertainty of where to access relevant information raised skepticism and eroded the trust in the government and authorities [ 32 , 33 , 34 ]. This uncertainty causing increased anxiety and stress, particularly related to health and economic fears, has also been observed in other countries [ 35 , 36 , 37 ]. For instance, a study in Singapore showed common responses to conflicting COVID-19 messages included fear, concern, panic buying and hoarding [ 35 ].…”
Section: Discussionmentioning
confidence: 74%
“…During the pandemic, confusion from mixed COVID-19 messages, different national guidelines, and the uncertainty of where to access relevant information raised skepticism and eroded the trust in the government and authorities [ 32 , 33 , 34 ]. This uncertainty causing increased anxiety and stress, particularly related to health and economic fears, has also been observed in other countries [ 35 , 36 , 37 ]. For instance, a study in Singapore showed common responses to conflicting COVID-19 messages included fear, concern, panic buying and hoarding [ 35 ].…”
Section: Discussionmentioning
confidence: 74%
“…Nevertheless, it included a score based on relevant local items describing lockdown positive appreciation. Fourth, as with many other studies dealing with the lockdown population health impact [ 3 , 34 , 39 , 40 ], our data were self-reported, which means that the health states of respondents were not confirmed by research examination or medical claims data. The health data may therefore be undermined by reporting bias such as a possible lack of awareness of the child’s health problems by the father compared to the mother.…”
Section: Discussionmentioning
confidence: 90%
“…In other words, our results are likely to be conservative. Third, the study questionnaire lacked a validated coping scale [ 40 ]. Nevertheless, it included a score based on relevant local items describing lockdown positive appreciation.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, our society is navigating through the post-COVID-19 era. The pandemic exacerbated economic inequalities both on a national and individual level, and these economic repercussions are also exerting impact on personal levels of happiness in the future [40,41]. Research on income distribution after COVID-19 revealed that employment income declined notably for single business owners, households with children under the age of 18 years, and single middle-aged households [28].…”
Section: Discussionmentioning
confidence: 99%